¹¹Basic_Calculus5
¹¹Basic_Calculus5
¹¹Basic_Calculus5
differential in
x
integral sign
integrand
Example
Verify that (3x − 2 x )dx = −3x − x + C .
−2 −1 2
solution
( )
Dx − 3x −1 − x 2 + C = 3x −2 − 2 x
⚫
5.2 Basic Theorems on
Antidifferentiation
Theorem 1 dx = x + C
Theorem 2
If n is any real number such that n −1,
n +1
then n x
dx =
x +C
n +1
Theorem 3
af (x )dx = a f (x )dx
where a is any real number.
Theorem 4 If f and g are defined on the
same interval, then
f (x ) g (x )dx = f (x )dx g (x )dx.
Theorem 5 If f1 , f2 , f3 ,. . ., fn are
defined on the same interval, then
f1 (x ) f 2 (x ) f 3 (x ) f n (x )dx
=
f1 (x )dx
f 2 (x )dx
f 3 (x )dx
f n (x )dx
Example 1
5
Evaluate
x 3 dx
solution
5
From Theorem 5.2.2 and with n =
3 ,
5 8
5 +1
x3 3x 3 .
x 3 dx = +C = +C
5 8
+ 1
3
Example 2
Evaluate ( + 11)dx .
solution
( + 11)dx = ( + 11) dx
.
= ( + 11)x + C
Example 3
5 1
Evaluate
3x − 5 x − x 2 dx
solution
3
6 2
3x 5x 2x 2
= − − +C
6 2 3
.
Example 4
Evaluate
(9 − 2x 7
)
− 10 x −2 dx
solution
(9 − 2x 7
− 10 x −2 ) dx = 9 x −
2 x8 x −1
− 10
−
+C
.
8 1
1
8
x
= 9 x − + 10 + C
4 x
Example 5
Evaluate ( x 2 x + 3 3 x dx )
1 1
solution
( )
x 2 x + 3 3 x dx = x 2 x 2 + 3x 3 dx
.
5 7
3 4
2x 2 3x 3
=
2 x 2 + 3x 3 dx = (2)
5
+ (3)
7
+C
5 7
4x 2 9x 3
= + +C
5 7
5.3 The Chain Rule for
Antidifferentiation
The Chain Rule
f (g (x ))g' (x )dx = F (g (x )) + C
Remark
g (x ) g' (x )dx = +C
n
n +1
Example 1
Evaluate
solution :
3 2 y − 5dy
(2 y − 5) 3 dy
1
3 2 y − 5dy =
Let u = 2 y − 5 du = 2dy
1
(2 y − 5)
1
3 dy = u3
du
=
1
2 u 3 du
.
2
4 4
1 3u 3 3u 3
= +C = +C
2 4 8
Substituting back
u = 2y − 5
4
3 2 y − 5dy 3(2 y − 5)
3
= +C
8
Example 2
Evaluate
(
x 4 x − 1 dx
3 4
)
2
solution:
(
x 4 x − 1 dx =
3 4
)
2
(4 x − 1) x dx
4 2 3
We let u = 4x −1 du = 16 x dx or du = x3dx.
4 3
Thus, ( x 4 x − 1 dx =
3 4
)
2
u2du
16
16
= u du = 1 u + C = (4 x − 1) + C
1 2 3 4 3
16 16 3 48
Example 3
Evaluate
s 2
s − 2ds
solution:
Let w = s − 2 dw = ds also s = w + 2
s 2
s − 2ds = (w + 2)2 wdw
=
(w 2
) 1
+ 4w + 4 w 2 dw
5
2
3 1
= w + 4w + 4w 2 dw
2
7 5 3
2w 2 2w 2 2w 2
= + (4) + (4 ) +C
7 5 3
7 5 3
2(s − 2 ) 2 8(s − 2 )2 8(s − 2 )2
= + + +C
7 5 3
Example 4
w − 1
2
Evaluate (w + w )
3
−1 2
2 dw
solution: w
Let u = w + w −1
−1
,
2
1 w
du = (1 − w )dw = 1 − 2 dw =
−2
dw
w
2
w
3 w − 1
2
Hence ( w + w −1
) 2 2 dw =
w
2(w + w ) +C
5 5
−1
3
2u 2 2
u du =
2
+C =
5 5
5.3b Antiderivative of
Logarithmic
and Exponential Function
⚫
⚫
⚫
1
න 𝑎𝑢 𝑑𝑢 = 𝑎𝑢 + 𝐶
𝑙𝑛𝑎
Example 4.
𝐿𝑒𝑡 𝑢 = 5 − 9𝑥
න 105 −9𝑥 𝑑𝑥 𝑑𝑢 = −9𝑑𝑥
1
− 𝑑𝑢 = 𝑑𝑥
9
1
= − 10𝑢 𝑑𝑢
9
−1
= 105−9𝑥 +𝐶
9𝑙𝑛10
න 𝑒 𝑢 𝑑𝑢 = 𝑒 𝑢 + 𝐶
Example 5.
𝐿𝑒𝑡 𝑢 = 2𝑥
න 8𝑒 2𝑥 𝑑𝑥 𝑑𝑢 = 2𝑑𝑥
1
𝑑𝑢 = 𝑑𝑥
2
𝑢 𝑑𝑢
= 8𝑒
2
= 4𝑒 2𝑥 + 𝐶
න 𝑒 𝑢 𝑑𝑢 = 𝑒 𝑢 + 𝐶
Example 6.
𝐿𝑒𝑡 𝑢 = 𝑥 4
3 𝑥4
න 𝑥 𝑒 𝑑𝑥 𝑑𝑢 = 4𝑥 3 𝑑𝑥
1
4𝑥 3 𝑑𝑢 = 𝑑𝑥
3 𝑢 1
= 𝑒 𝑥 4𝑥 3 𝑑𝑢
1
= 𝑒 𝑢 𝑑𝑢
4
1 𝑢 1 𝑥4
= 𝑒 +𝐶 = 𝑒 +𝐶
4 4